PRESSURE GRADIENT PREDICTION IN PARTICLE-LIQUID TWO-PHASE FLOW - Aybar, Hikmet S.; Sharifpur, Mohsen; Vaziri, Roozbeh (Amer Soc Mechanical Engineers, 2009)
The prediction of pressure gradient in two-phase flows is an essential step in the design of a variety of industrial applications. In this study, it is developed the idea that porous media could be a particle-liquid two-phase flow with saturation of the particles. Thus, by setting up an experimental apparatus, it is investigated the behavior of particle-liquid two-phase flow in the cases of dilution of the particles to rich porous media. By using the experimental results an empirical expression is offered for the prediction of pressure gradient of particle-liquid two-phase flow.
ASME International Mechanical Engineering Congress and Exposition -- OCT 31-NOV 06, 2008 -- Boston, MA
Keywords: Simulation; Pipes